T tysonrss May 2010 43 0 May 20, 2010 #1 Hi guys could someone help with this question? Use the technique of completing the square to transform the quadratic equation into the form (x + c)2 = a. 6x2 + 36x + 18 = 0

Hi guys could someone help with this question? Use the technique of completing the square to transform the quadratic equation into the form (x + c)2 = a. 6x2 + 36x + 18 = 0

D DrDank May 2010 20 8 May 20, 2010 #2 \(\displaystyle 6x^2+36x+18=0\) \(\displaystyle 6x^2+36x+54-36=0\) \(\displaystyle 6x^2+36x+54=36\) \(\displaystyle 6(x^2+6x+9)=36\) \(\displaystyle 6(x+3)^2=36\) \(\displaystyle (x+3)^2=6\) Reactions: tysonrss

\(\displaystyle 6x^2+36x+18=0\) \(\displaystyle 6x^2+36x+54-36=0\) \(\displaystyle 6x^2+36x+54=36\) \(\displaystyle 6(x^2+6x+9)=36\) \(\displaystyle 6(x+3)^2=36\) \(\displaystyle (x+3)^2=6\)